2016
DOI: 10.1073/pnas.1602591113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of viral RNA-dependent RNA polymerase catalysis and translocation

Abstract: Viral RNA-dependent RNA polymerases (RdRPs) play essential roles in viral genome replication and transcription. We previously reported several structural states of the poliovirus RdRP nucleotide addition cycle (NAC) that revealed a unique palm domain-based active site closure mechanism and proposed a six-state NAC model including a hypothetical state representing translocation intermediates. Using the RdRP from another human enterovirus, enterovirus 71, here we report seven RdRP elongation complex structures d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
207
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(228 citation statements)
references
References 57 publications
(85 reference statements)
16
207
0
1
Order By: Relevance
“…4C and D). These data, in general, suggest that both SUMOylation sites in 3D may modulate EV71 polymerase activity, despite their differences in structural properties based on available crystallographic data (56,64).…”
Section: D Polymerase Is Sumoylated During Ev71 Infectionmentioning
confidence: 79%
See 2 more Smart Citations
“…4C and D). These data, in general, suggest that both SUMOylation sites in 3D may modulate EV71 polymerase activity, despite their differences in structural properties based on available crystallographic data (56,64).…”
Section: D Polymerase Is Sumoylated During Ev71 Infectionmentioning
confidence: 79%
“…The plasmids for the expression of WT 3D and its variants were transformed into Escherichia coli strain BL21(DE3)(pCG1) (kindly supplied by Craig Cameron) for expression (54). The bacteria were cultured and purified as described previously, except that the induction condition before harvesting was 11 h at 25°C (56). The preparation of the 33-nucleotide RNA template (T33) was as described previously (57,58).…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Crystal structures of nucleic acid polymerase superfamily members have indicated that there is a reorientation of the triphosphate of the incoming nucleotide following initial binding to properly align the ␣-phosphate for nucleophilic attack by the primer 3Ј-OH (10,48) (Fig. 12).…”
Section: Discussionmentioning
confidence: 99%
“…There is then a re-alignment of the NTP triphosphate and conserved residue Asp-233 around the two metal ions (10). Residues in motif F, including Lys-167 and Arg-174, are also involved in binding the triphosphate.…”
mentioning
confidence: 99%